Adult burn survivors' personal experiences of rehabilitation: An integrative review - Kornhaber, R.; Wilson, A.; Abu-Qamar, Ma'en; McLean, L. (Pergamon, 2014)
Burn rehabilitation is a lengthy process associated with physical and psychosocial problems. As a critical area in burn care, the aim was to systematically synthesise the literature focussing on personal perceptions and experiences of adult burn survivors’ rehabilitation and to identify factors that influence their rehabilitation. Studies were identified through an electronic search using the databases: PubMed, CINAHL, EMBASE, Scopus, PsycINFO and Trove of peer reviewed research published between 2002 and 2012 limited to English-language research with search terms developed to reflect burn rehabilitation. From the 378 papers identified, 14 research papers met the inclusion criteria. Across all studies, there were 184 participants conducted in eight different countries. The reported mean age was 41 years with a mean total body surface area (TBSA) burn of 34% and the length of stay ranging from one day to 68 months. Significant factors identified as influential in burn rehabilitation were the impact of support, coping and acceptance, the importance of work, physical changes and limitations. This review suggests there is a necessity for appropriate knowledge and education based programmes for burn survivors with consideration given to the timing and delivery of education to facilitate the rehabilitation journey.